Cytokine expression in subjects with Mycobacterium avium ssp. paratuberculosis positive blood cultures and a meta-analysis of cytokine expression in Crohn’s disease - Kuenstner, J. Todd; Xu, Qiang; Bull, Tim J.; Foddai, Antonio C. G.; Grant, Irene R.; Naser, Saleh A.; Potula, Raghava; Zhang, Peilin; Shafran, Ira; Akhanli, Serhat Emre; Khaiboullina, Svetlana; Kruzelock, Russell (Frontiers in Cellular and Infection Microbiology, 2024)
Objectives: 1) Culture Mycobacterium avium ssp. paratuberculosis (MAP) from blood, 2) assess infection persistence, 3) determine CD cytokine expression, 3) compare CD cytokine expression to tuberculosis, and 4) perform a meta-analysis of cytokine expression in CD.The Temple University/Abilene Christian University (TU/ACU) study had a prospective case control design with 201 subjects including 61 CD patients and 140 non-CD controls. The culture methods included the MGIT, TiKa and Pozzato, and were deemed MAP positive, if IS900 PCR positive. A phage amplification assay was also performed to detect MAP.Cytokine analysis of the TU/ACU samples was performed using Simple Plex cytokine reagents on the Ella ELISA system. Statistical analyses were done after log transformation using the R software package. The meta-analysis combined three studies.Results: Most subjects had MAP positive blood cultures by one or more methods in 3 laboratories. In our cytokine study comparing CD to non-CD controls, IL-17, IFNγ and TNFα were significantly increased in CD, but IL-2, IL-5, IL-10 and GM-CSF were not increased. In the meta-analysis, IL-6, IL-8 and IL-12 were significantly increased in the CD patients. Conclusions: Most subjects in our sample had MAP infection and 8 of 9 subjects remained MAP positive one year later indicating persistent infection. While not identical, cytokine expression patterns in MAP culture positive CD patients in the TU/ACU study showed similarities (increased IL-17, IFNγ and TNFα) to patterns of patients with TB in other studies, indicating the possibilities of similar mechanisms of pathogen infection and potential strategies for treatment.